Layne & Bowler Corporation Exhibit at the Palace of Machinery (Geo. Rice & Sons)
On verso: An educational exhibit showing in actual operation Patent Deep Well Turbine Centrifugal Pumps which operate with much less power than other pumps built to operate under same conditions.